Broad spectrum triazoles for invasive mould infections in adults: Which drug and when? - Jenks, Jeffrey D; Mehta, Sanjay R; Hoenigl, Martin (Medical mycology (Oxford), 2019)
Invasive mould infections are an increasing cause of morbidity and mortality globally, mainly due to increasing numbers of immunocompromised individuals at risk for fungal infections. The introduction of broad spectrum triazoles, which are much better tolerated compared to conventional amphotericin B formulations, has increased survival, particularly in invasive mould infection. However, early initiation of appropriate antifungal treatment remains a major predictor of outcome in invasive mould infection, but despite significant advances in diagnosis of these diseases, early diagnosis remains a challenge. As a result, prophylaxis with mould-active triazoles is widely used for those patients at highest risk for invasive mould infection, including patients with prolonged neutropenia after induction chemotherapy for acute myeloid leukemia and patients with graft-versus-host-disease. Posaconazole is the recommended drug of choice for antimould prophylaxis in these high-risk patients. Voriconazole has its primary role in treatment of invasive aspergillosis but not in prophylaxis. Recently, isavuconazole has been introduced as an excellent alternative to voriconazole for primary treatment of invasive aspergillosis in patients with hematological malignancies. Compared to voriconazole, isavuconazole and posaconazole have broader activity against moulds and are therefore also an option for treatment of mucormycosis in the presence of intolerance or contraindications against liposomal amphotericin B.